Assessment of Knowledge, Attitude and Practice towards Dispensing of Antibiotics and Over the Counter Drugs among Community Pharmacists in Guntur, Andhra Pradesh - Pelluri, Ranakishor; Thummapudi, Monikasurya; Paritala, Harika; Kumar, Thota Sai Kiran; Sulthana, Raziya; Radha, Chinta Indu; Chandu, Madhuri; Rebba, Sai Susmitha; Kara, Amrutha; Rayapati, Geethika; Velavarthipati, Prudhvi Sai; Doddapaneni, Sruthi; et al. (Journal of Pharmacy Practice and Community Medicine)
Aim: To assess the knowledge, attitude, and practice (KAP) concerning dispensing pattern of antibiotics and OTC medication among the retail dispersers in community pharmacies. Materials and Methods: A cross-sectional study was performed from March 2021 to August 2021. Simulated patient (SP) based face-to-face interviews were conducted with validated structured questionnaires. Results: During our interview, we noticed only 60% of registered pharmacists (RPs) and 40% of non-RPs were working in community pharmacies. Among the RPs, 35 were D.Pharm and 62 were B.Pharm graduates. The average correct answer to antibiotic questionnaires provided by dispensers with D.Pharm (39.2%), B.Pharm (47.7%) and Non-Pharmacists (38.4%). Among the respondents, the KAP against antibiotic questionnaires No. 1 and 4 are statistically significant (p<0.05). Similarly, 44.5% of D.Pharm, 56.6% of B.Pharm and 42.2% of Non-Pharmacists responded to OTC questionnaires. The OTC questionnaire No. 1,4 and 7 are not statistically significant (p>0.05) among responders. Conclusion: In our findings, 40% of non-Pharmacists were running the pharmacies. On an average, they have less than 50% of KAP towards antibiotics and OTC medications among pharmacists and non-pharmacists. To overcome this, pharmacists should undergo need continual professional development programs and non-pharmacist must require a formal pharmacy education.
Keywords: Over-the-counter; Pharmacy Practice; Simulated patient; Self-medication; South India